A Controversial Painting by Bartolomeo Montagna: A New Hypothesis for a Notable Piece in the Early Production of the Head Painter of Vicenza - de Zuani, Laura (Actual Problems of Theory and History of Art, 2016)
The essay presents the painter Bartolomeo Montagna (1452–1523), founder of the Renaissance Vicentine school of painting. The paper starts from his early production side by side with Gianfrancesco Somaio, to the direct comparison with Venetian innovation carried on by Giovanni Bellini. Bartolomeo Montagna got acquainted with the Venetian master during his two journeys to Venice between 1469 and 1483. Looking at his 1480s production, bounded to the Venetian experience and to Antonello da Messina’s heritage, the report examines the complex connections between Bartolomeo Montagna, the inlayer Pierantonio degli Abati and the architect Lorenzo da Bologna. The collaboration between these three artists started with the great construction of the Vicentine Church of Saint Bartholomew, and then it went on thanks to the most important artistic workshop in Padua at the end of the 15th century. The first years of the painter’s career were examined through archival documents and stylistic analysis in order to confirm a new hypothesis on his patrons. After explaining the complex cultural contributions matched by the painter, we move on to the particular case: a signed and dated painting (1487) which obviously does not correspond to this date. The paper offers a new hypothesis regarding the subject of the painting The Virgin and Child with Saint Sebastian and Saint Roch, its date and the unusual position of the inscription (on the reverse side) searching for a more suitable place for this painting in Montagna’s artistic career. A new document, regarding Montagna’s masterpiece in Saint Bartholomew, recently brought to light by an Italian archivist Manuela Barausse, is also helpful in this case. The essay finally shows how an apparently well-defined case leads to a long journey, in order to comprehend the meaning of the artistic creation.
Keywords: Bartolomeo Montagna; Vicenza; Venetian art; Saint Roch; Lorenzo da Bologna; pestilence